2010
DOI: 10.1021/jp108534d
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Photophysics in a Low Band Gap Polymer with High Photovoltaic Efficiency

Abstract: We report an experimental investigation of a newly synthesized polymer, PNDT-DTPyT, with a 1.55 eV band gap tuned for optimal photovoltaic performance. Several time-resolved optical spectroscopies are used to examine fundamental photophysics in pure polymer films. Clear signatures of a distribution in photoexcitation sizes are found in steady state absorption and fluorescence measurements conducted from 100 to 300 K. Electronic structure calculations are combined with an empirical model to establish that, on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
(174 reference statements)
1
6
0
Order By: Relevance
“…Pyridinochalcogenadiazole PTA and PSeA with a fused pyridine ring would be more electron-deficient than the benzoannulated analogues, and thus, a stronger donor-acceptor interaction was anticipated in the present polymers. [20][21][22] Indeed, both the DTS-and DTG-PTA alternate polymers synthesized in this study showed absorption bands at approximately 740 nm in solution, which were red-shifted from those of pDTS-BTA and pDTG-BTA with the same substituents on the center metals, as reported previously. 8,10,18…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Pyridinochalcogenadiazole PTA and PSeA with a fused pyridine ring would be more electron-deficient than the benzoannulated analogues, and thus, a stronger donor-acceptor interaction was anticipated in the present polymers. [20][21][22] Indeed, both the DTS-and DTG-PTA alternate polymers synthesized in this study showed absorption bands at approximately 740 nm in solution, which were red-shifted from those of pDTS-BTA and pDTG-BTA with the same substituents on the center metals, as reported previously. 8,10,18…”
Section: Introductionsupporting
confidence: 85%
“…Chlorobenzene and ether used as the reaction solvents were distilled from CaH 2 and sodium/benzophenone ketyl, respectively, and stored over activated molecular sieves until use. The monomers DTSSn 2 , 4 DTGSn 2 16 and PTABr 2 21,22 were prepared as reported in the literature. Nuclear magnetic resonance (NMR) spectra were recorded on Varian 400-MR and System-500 spectrometers (Agilent Inc., Santa Clara, CA, USA).…”
Section: Experimental Procedures Generalmentioning
confidence: 99%
“…Previous experiments have demonstrated that the optical absorption of the organic dyes is red-shifted on extension of the π conjugation by the incorporation of electron-deficient segments [22,24]. You and coworkers have synthesized a series of narrow band gap polymers incorporating NDT units for organic solar cells [29][30][31][32]. For example, recently they constructed a library of polymers employing the NDT and BT units as the weak donor and the strong acceptor, respectively.…”
Section: Excitationsmentioning
confidence: 99%
“…A smaller HOMO-LUMO gap is needed to achieve a higher JSC, while the low HOMO energy level should still be maintained for efficient dye regeneration. You and coworkers have reported that the LUMO of donor-acceptor copolymers largely locates on the acceptor moiety, and the bandgap can be reduced by incorporating a electron deficient unit to lower the LUMO while at the same time maintain the HOMO energy level [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…To exploit high‐performance photovoltaic materials, great efforts have been devoted to low‐bandgap polymers and broad‐absorption polymers 7, 8. Although significant advances have been achieved in improving the PCEs of PSCs by using new active layer materials,9–16 there is still much to do before the realization of practical applications of PSCs. Limiting factors include the narrow absorption band of conjugated polymers, the low photon–electron conversion rate, the unmatched molecular energy levels, and the low‐charge‐carrier mobility of the polymer photovoltaic materials.…”
Section: Introductionmentioning
confidence: 99%